IPO Underpricing in the Russian Stock Market - Sergey Kondratev; Elizaveta Batalova; Olga Frolova (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2024)
This paper investigates stock underpricing in the Russian capital market during initial public offerings in the present-day situation. The econometric study of initial public offerings in the Russian market for 2006–2024 shows that such factors as dividend policy, technological profile of the company, and the difference between the actual and expected offering price increase IPO underpricing. Additionally a positive correlation between the capital raised by the company and the reduction of the underpricing IPO effect is revealed: large companies have more stable financial indicators, which brings their valuation closer to the real value in the market.